Toksisitas Senyawa Tembaga(II)Klorida Dihidrat Terhadap Sel Kanker Payudara T74D Secara in vitro - Teguh Hari Sucipto; Harsasi Setyawati; Fahimah Martak (Universitas Muhammadiyah Surabaya, 2018)
Cancer is a transformation of normal cells in the body into malignancy due to the induction of carcinogens. Breast cancer is the second leading cause of death in Indonesia. The field of treatment with inorganic compounds has been widely developed and shows better anticancer activity than organic compounds. This research aims to know the toxicity level of copper value of 29.021 μg/ml. The value of IC 50 obtained <100 μg/ml so that the copperCancer is a transformation of normal cells in the body into malignancy due to the induction ofcarcinogens. Breast cancer is the second leading cause of death in Indonesia. The field oftreatment with inorganic compounds has been widely developed and shows better anticanceractivity than organic compounds. This research aims to know the toxicity level ofcoppervalue of 29.021 μg/ml. The value of IC50obtained<100 μg/ml so that the copper